What Do Academic Achievement Analyses Say about Primary and Secondary Education? - Hisam Kim (Korea Development Institute (KDI), 2013)
High investment in school education does not necessarily lead to higher academic achievement. Therefore, an increase in students' motivation and other contributory causes is more important than an increase in quantitative input. - Academic achievement is a key indicator for measuring the outcomes of education. - If the teacher evaluations filled out by students for professional development provides effective feedback, it can contribute to improving academic achievement - Reducing the number of students per teacher will not necessarily guarantee improvement of academic achievement without innovative teaching methods. - Level-based instruction has limitations under a relative evaluation system in which the students take identical tests regardless of their levels, aptitude, and future plans. - The negative impact of coed schools partly stems from the students' loss of study hours and lack of learning flow while attending high school. - Teachers and parents should make every effort to help students develop the capacity for self-directed learning, which is more effective than private education at increasing scores with each increasing grade level. - In order for coed schools to achieve their educational potential, they must first establish a gender-sensitive educational environment, accompanied by sophisticated management.
Keywords: 330